2005
DOI: 10.1007/s00705-005-0564-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and PrP genotype target of scrapie in clinically healthy sheep of Massese breed in the framework of a scrapie eradication programme

Abstract: The application of a selective culling programme in two scrapie affected flocks of Massese breed sheep is described. The genetic susceptibility of this breed and the sensitivity of different diagnostic methods in the pre-clinical diagnosis of scrapie were also investigated. Overall, 2,068 clinically healthy sheep underwent PrP genotyping, providing the basis for selective culling. The prevalence of scrapie infection was investigated in susceptible sheep by two independent diagnostic methods. All the sheep olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…These results are in contrast to previous studies carried out in Scotland (Jeffrey et al, 2002) and Iceland (Thorgeirsdottir et al, 2002) in which these genotypes seemed to be more resistant to a scrapie infection. However, the results reported here are in accordance with the results from an outbreak in Italy (Vascellari et al, 2005). The most probable explanation for this difference is that scrapie strains with a bias towards different genotypes had been going round the flocks in question.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in contrast to previous studies carried out in Scotland (Jeffrey et al, 2002) and Iceland (Thorgeirsdottir et al, 2002) in which these genotypes seemed to be more resistant to a scrapie infection. However, the results reported here are in accordance with the results from an outbreak in Italy (Vascellari et al, 2005). The most probable explanation for this difference is that scrapie strains with a bias towards different genotypes had been going round the flocks in question.…”
Section: Discussionsupporting
confidence: 90%
“…This investigation revealed that 30% of these animals were preclinically scrapie-infected and that 7.4% of them were PrP Sc -positive only at the peripheral sites but not in the brain stem, which is routinely tested. This prevalence is within the range of 5% to 30.3% previously reported in similar studies (Jeffrey et al, 2002;Thorgeirsdottir et al 2002;Ersdal et al 2003;Vascellari et al 2005;Gonzalez et al, 2006). The classical scrapie prevalence in a flock depends on different factors: a) length of time period after the introduction of the infection into the flock; b) husbandry measures (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…However, the simultaneous presence of isoleucine at codon 142 and asparagine at codon 146, as obtained in our study (Table 2), were found to be associated with an atypical TSE in Swiss goats [39]. In addition, the replacement of arginine by histidine in one rural goat at codon 154 (Table 2) has a variable protective effect against TSE, depending on the goat breed [40,41]; actually this mutation (R→H) provided some TSE-protection in Dman and Chaouni goats [42] leading to less frequency in TSE of goats [43]; on the contrary, this substitution (R→H) at codon 154 created a risk factor of atypical TSE in goats [44].…”
Section: Polymorphism In Prion (Prp) Genesupporting
confidence: 62%
“…Polymorphisms at the ovine PrP gene are associated with susceptibility to scrapie. Selection against some PrP alleles is the basis of current breeding programmes implemented to control this disease (Vascellari et al, 2005;Hunter, 2007;Dawson et al, 2008). Sawalha et al (2009) showed a strong significant association of PrP genotypes with coat colour in Badgerfaced Welsh Mountain and Shetland sheep, probably due to Agouti locus alleles.…”
Section: Discussionmentioning
confidence: 99%